Utilização de um ambiente virtual de aprendizagem: um estudo na perspectiva da prática docente - Pimenta, Iris Linhares (2012)
Advances related to information technology are visible and inherent to the management of contemporary organizations, regardless of industrial action. Synchronized with this dynamic, educational institutions are incorporating technological tools that assist its management and academic support to teachers in teaching and interaction with the students. Given that technological innovations are not always taken homogeneously and with the same degree of coverage, remain current and relevant studies on how these technologies are being used in academia. The objective of this research is to identify the usage profile of the functionality of a virtual learning environment related to teaching (undergraduate or postgraduate), demographic variables (age and gender) and institutional (time of admission and academic center of origin.) The methodology applied to the study is descriptive and quantitative. The research is characterized as census, covering all 2152 teachers of undergraduate and graduate students of the Federal University of Rio Grande do Norte, Brazil, who accessed the virtual classes of the Integrated Management of Academic Activities. The study findings revealed that there is a statistically significant difference regarding the use of these tools to teachers who work with undergraduate (49.3%) compared to graduate (6.6%). Regarding gender, women (40.1%) use the system more than men (38.5%). It was also observed that the younger teachers, aged 37 years, are the most active users (42.5%) of the Virtual Class with respect to their elders. For teachers with up to three years time of admission to the UFRN, the pattern of use is more advanced than those with more seniority, as well as the faculty of the Center for Science and Technology are the least likely to use the tools available in relation to other academic centers. It is hoped that with this study managers can direct actions to improve and expand the use of this environment by teachers